2021
DOI: 10.1080/2474736x.2020.1868946
|View full text |Cite
|
Sign up to set email alerts
|

Stuck between the modern and the terrestrial: the indignation of the youth for climate movement

Abstract: The dramatic impacts of climate change have pushed thousands of young activists to shout out their indignation. These mobilizations have become the symbol of our 'tipping era': a clash of worlds between attachments to modernity and attempts to become 'terrestrial' (Latour, 2018) to stay within ecological boundaries. In this field, there has been an increasing body of theoretical work but empirical research is still in its infancy, providing little evidence of this ongoing struggle and what we can learn from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 38 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…In particular, the climate activists from "Fridays For Future" to "Extinction Rebellion" refer to the existential dimension, perceiving climate change as a threat to their future. The empirical research on this movement is still in its infancy (Fisher 2019;Knops 2021) but some survey-based studies suggest that participation of young people in climate strikes is related to risk perception (Brügger et al 2020;Misch et al 2021), in line with earlier studies (Wang et al 2018). The youth movement has identified climate change as the greatest existential threat to the Earth and to human beings, and they consider this threat as a moral element of their narrative (Han and Ahn 2020).…”
Section: Civil Society Climate Movementmentioning
confidence: 63%
See 1 more Smart Citation
“…In particular, the climate activists from "Fridays For Future" to "Extinction Rebellion" refer to the existential dimension, perceiving climate change as a threat to their future. The empirical research on this movement is still in its infancy (Fisher 2019;Knops 2021) but some survey-based studies suggest that participation of young people in climate strikes is related to risk perception (Brügger et al 2020;Misch et al 2021), in line with earlier studies (Wang et al 2018). The youth movement has identified climate change as the greatest existential threat to the Earth and to human beings, and they consider this threat as a moral element of their narrative (Han and Ahn 2020).…”
Section: Civil Society Climate Movementmentioning
confidence: 63%
“…However, the thinking and theoretical fundaments underlying the narratives of the climate movement differ from the scientific understanding of climate risk. Recent empirical and theoretical research on the youth climate movement identified narratives of vernacular eschatology and postapocalyptics where temporality and imaginaries of collapse play an important role (Knops 2021 ; Friberg 2022 ). The term existential thus refers more to the need of a fundamental change which is also reflected by the constant critique of capitalism by the climate movement, and the request of drastic measures in line with changes in societal structures and economy, illustrated by the well-known slogan “system change not climate change” (SCNCC 2021 ).…”
Section: Definitions Concepts and Narratives Of Existential Risksmentioning
confidence: 99%
“…Negative emotions also play a vital role in the messages communicated by many environmental movements. For example, activists at Youth for Climate express indignation by invoking younger generations as victims of political procrastination and by framing perceived economic injustices in moral terms by emphasizing inequalities and overconsumption (Knops, 2021). Extinction Rebellion, an international movement, campaigns for radical change and encourages activist participation by openly communicating fears about the future of the planet (Furlong & Vignoles, 2021; Slaven & Heydon, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…(Von der Leyen, 2019, p. 5) Hence, the Green Deal was at least partly a response to one of the main political messages of the European parliamentary elections of April 2019, in which Green parties in large Western member states significantly increased their support by campaigning on a platform that focused on climate action (Mudde, 2019). Most significantly, the Green Deal was inspired by the emergence and surging popularity of youth grassroots movements such as Fridays for Future and Youth Strike for Climate (Knops, 2021). The rise of Fridays for Future and Youth Strike for Climate was an important source of environmental turbulence because they constituted unprecedented, transboundary civil society movements that called for radical governance responses to climate change across numerous policy areas.…”
Section: The European Green Deal: a Response To Environmental And Organisational Turbulence?mentioning
confidence: 99%